Sejarah Islam Masa Modern di Mesir (Pembaharu di Bidang Pendidikan) - Andriani, Hesti; Susmihara, Susmihara (LP2M Universitas Islam Ahmad Dahlan, 2024)
This article discusses the history of modern Islam in Egypt as well as reformers in the field of education. This research uses library research with a qualitative approach. Egypt only became an Islamic city when Umar became caliph. Over time, Egypt experienced development in the modern era, marked by the emergence of reforming figures. Renewal in Islam is a necessity in life to overcome the life problems that society needs at that time. This reform was carried out by reforming figures who proved that Islam can answer society's problems in all times and Islamic teachings can make a positive contribution to every era's development. Educational reform was pioneered by figures with their own ideas about education, including: Muhammad Ali Pasha, Al-Tahtawi, Muhammad Abduh, Rasyid Ridha, Jamaluddin Al-Afgany, Ali Mubarak, Thaha Husain, and so on.